Agents containing chlorhexidine in dentistry - Lebedeva S.N.; Zemlyanichenko М.К. (Саратовский научно-медицинский журнал, 2011)
Aclinical definition of the efficacy of chlorhexidine-containing means for reducing the risk of dental caries and gingivitis with plastic caps. Chlorhexidine is an effective antimicrobial agent for the formation of individual programs for the prevention of dental caries